Young students and desire to social entrepreneurship: the impact of government's role. (9th August 2022) - Sukumar, Arun; Jafari-Sadeghi, Vahid; Xu, Zimu; Tomlins, Richard
The main aim of the research was intended in assessing the role of the Indonesian Government towards the promotion of social entrepreneurship in the country. The research was focused on addressing the level of awareness about the concept of social enterprise and what it means in Indonesia, especially among young students. For achieving this aim, a survey was conducted among students in Jakarta, Indonesia. The survey reflected the assessment of government role in the promotion of social entrepreneurship in Indonesia. The results noted that when it came to social entrepreneurship, it is the government that acts as a vital role in communication, what a social enterprise is and its role to the members of the society. From the regression analysis, it was identified that there is a significant relationship between the promotion of social entrepreneurship and the role of the Indonesian Government. However, the study also identifies that while the promotion of social enterprise is essential, the role of innovation and its link to the building resilient social enterprises needs more attention.